2012
DOI: 10.1142/s0217732312500174
|View full text |Cite
|
Sign up to set email alerts
|

Collision Energy in the Center-of-Mass Frame for Rotating and Accelerating Black Holes

Abstract: The center-of-mass (CM) energy of collision for two uncharged particles falling freely from rest at infinity is investigated in the background of charged, rotating and accelerating black hole. It is found that the CM energy of collision is unlimited at the acceleration horizon and at the event horizon (in the extremal case) if one of the colliding particles has critical angular momentum and the other one has a proper angular momentum such that the particle can reach the horizon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…if it is satisfied initially, then it is always valid, provided that θ(τ ) and r (τ ) are controlled by Eqs. (27) and (28). Let us discuss the symmetries of Eqs.…”
Section: Dynamics Of a Charged Particlementioning
confidence: 99%
See 1 more Smart Citation
“…if it is satisfied initially, then it is always valid, provided that θ(τ ) and r (τ ) are controlled by Eqs. (27) and (28). Let us discuss the symmetries of Eqs.…”
Section: Dynamics Of a Charged Particlementioning
confidence: 99%
“…In the vicinity of extremal Kerr black hole, they have found that infinite centerof-mass energy (CME) can be achieved during the collision of particles. The BSW effect has been studied for different black hole spacetimes [18][19][20][21][22][23][24][25][26][27][28][29][30]. In this paper we obtain the CME expression for the colliding particles near horizon of Schwarzschild-like black hole surrounded by quintessence matter and BSW effect is studied for both neutral and charged particles.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the CME depends on the spin parameter a and NUT (Newman-Unti-Tamburino) charge n. Exact Lense-Thirring (LT) precession and causal geodesics in the inner-most stable circular orbit (ISCO) in a KerrTaub-NUT black hole was studied in [18][19][20]. The CME of the collision for two uncharged particles falling freely from rest at infinity in the background of a charged, rotating and accelerating black hole was investigated in [21].…”
Section: Jhep05(2015)147mentioning
confidence: 99%
“…They also proved that BH having no event horizon or singularity can also have high CME for particular values of parameters m and q (2012c). Hussain (2012) found that the CME of colliding particles in Plebanski and Demianski BH (extremal) with zero NUT parameter is unlimited at the acceleration and event horizons. Zaslavskii (2010aZaslavskii ( , 2010bZaslavskii ( , 2011 studied the universal property for particle acceleration and generalized the BSW effect for dirty BHs with nonequatorial motion of colliding particles.…”
Section: Introductionmentioning
confidence: 99%